The Development of Radioactive Waste Management Policies in Indonesia - Elizabeth Fitzgerald, Samantha; Lewiandy, Lewiandy (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, the management of radioactive waste should be carried out safely to prevent harmful impacts on the environment and human health. In reality, radioactive waste management in Indonesia faces challenges regarding clear standards and procedures, despite existing regulations. This study aims to analyze the development of radioactive waste management policies in Indonesia, specifically comparing Government Regulation No. 27 of 2002 and Government Regulation No. 61 of 2013. The research uses a normative legal research method with an approach that analyzes regulations and the relevance of policies to international safety standards. The findings show that Government Regulation No. 61 of 2013 provides a more detailed and structured management framework compared to Government Regulation No. 27 of 2002. The newer regulation adopts a more detailed classification of radioactive waste, as well as stricter licensing and monitoring procedures, which in turn enhance the effectiveness of management and safety.